Persistent Hemodynamic Depression After Carotid Artery Stenting: A Review and Update. (October 2022) - Liu, Xiaowei; Zheng, Peilin; Xu, Xuejun; Tu, Yiting
According to the American Heart Association, ischemic stroke is the second leading cause of death globally and is responsible for approximately 11% of deaths. Carotid endarterectomy (CEA) is the standard treatment for moderate or severe extracranial internal carotid artery (ICA) stenoses. With the development of materials and technology in neurointervention, the Centers for Medicare and Medicaid Services (CMS) have proposed that carotid artery stenting (CAS) can serve as an alternative treatment for CEA. As CAS is widely used worldwide, comorbidities, especially persistent hemodynamic depression (PHD) and stroke, have attracted public attention. In this review, we summarized the current advances in PHD after CAS. A better understanding of CAS-related PHD may inspire the design of potential prognostic and therapeutic tools.